1983
DOI: 10.1128/jcm.18.3.722-724.1983
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Staphylococcus aureus in blood cultures by thermonuclease testing

Abstract: The detection of thermonuclease activity in 86 blood culture samples containing gram-positive cocci showed 100% correlation with the subsequent identification of the isolate as Staphylococcus aureus by the coagulase test. No positive thermonuclease results were found with 66 samples containing coagulase-negative staphylococci and 56 samples containing other gram-positive organisms. The thermonuclease test provides a rapid, reliable method to identify S. aureus in blood cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 23 publications
(18 reference statements)
2
13
0
1
Order By: Relevance
“…Previously, we have tested additional non-S. aureus isolates, some of which were also positive in the thermonuclease test (4,5,9). Although the thermonuclease test has been used to identify S. aureus isolates from human and veterinary clinical specimens, including same-day identification of blood culture isolates (21,24), environmental or dietary product isolates (14, 23), our results substantiate the lack of specificity of this test for S. aureus. Furthermore, the seroinhibition test based on polyclonal anti-TNase serum failed to confirm the species S. aureus, since this antiserum also inhibited the activity of non-S. aureus TNases to a considerable extent.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previously, we have tested additional non-S. aureus isolates, some of which were also positive in the thermonuclease test (4,5,9). Although the thermonuclease test has been used to identify S. aureus isolates from human and veterinary clinical specimens, including same-day identification of blood culture isolates (21,24), environmental or dietary product isolates (14, 23), our results substantiate the lack of specificity of this test for S. aureus. Furthermore, the seroinhibition test based on polyclonal anti-TNase serum failed to confirm the species S. aureus, since this antiserum also inhibited the activity of non-S. aureus TNases to a considerable extent.…”
Section: Discussionmentioning
confidence: 59%
“…The thermonuclease test for DNA degradation by the thermostable nuclease (TNase) produced by S. aureus, originally described by Lachica et al (19), is regarded as reliable for identification of this bacterium by direct examination of blood cultures (21,24). However, strains of the species S. schleiferi, S. carnosus, S. intermedius, S. hyicus, S. caprae, and S, capitis may produce TNases (10,17,18).…”
mentioning
confidence: 99%
“…Direct detection of ORSA in blood cultures. The blood culture vials showing growth of gram-positive cocci and demonstrating thermonuclease activities indicated that there were S. aureus cells in these vials (17). A total of 96 such blood cultures were used for direct detection of ORSA by the impedance method.…”
Section: Effect Of Oxacillin Concentration On Impedance Curvesmentioning
confidence: 99%
“…The susceptibility of S. aureus to lysostaphin was reported to be an excellent way to distinguish this organism from CNS (157,158). Subsequently, testing with thermonuclease, a heat-stable DNase produced by S. aureus, was reported to be a rapid, accurate identification method (102,137). The test could be performed from either standard blood culture broths or BACTEC bottles with a positive growth index (144).…”
Section: Biochemical Testsmentioning
confidence: 99%